Visitor's perception and satisfaction establishing architectural guidelines enhancing tourism development in Bislig City - Layno, Kenneth V. (2016)
Tourism plays a vital role in today?s economic activities. Success of is credited to visitors and in their level of satisfaction. Hence, the three main objectives of this research were; a. to identify the general perception of visitors of Bislig City as a tourist destination, b. to identify which underlying factors significantly affect their over-all experience; and c. to determine how the attitude and satisfaction of residence towards tourism development. The perception of potential visitors was relatively high on the factors expected expenditures, quality of accommodation and quality of food service. The perceptions of actual visitors were relatively high on the factors geographical features, expected expenditure, quality of accommodation and safety and security. Using independent sample t-test, it emerged that the actual travel to and from the city leads to significant negative effect on the level of perceptions specifically on the factors quality of infrastructures, hospitality qualities of LGUs and the quality of transportation. Visitor?s level of satisfaction was obtained through a survey questionnaire. Using regression analysis, the attributes of satisfaction which have significant effect on their general experience are accessibility, built environment, tourism staff, commercial considerations, information, physical environment and accommodation. All the items of each attribute of visitor satisfaction were also regressed and showed 19 items to have significant effect on the over-all satisfaction of visitors ( state of maintenance of tourists? signs and symbols, diversity and quality of attractions, distance from the destination, equipment and infrastructure safety, level of noise, state of maintenance on access roads and public and private services, etc.) this study also conducted a focus group discussion to determine local residents? attitude and level of satisfaction towards tourism development in Bislig City. It was discovered that local residents were generally satisfied, as long as it personally benefits them but with reservations on the possible adverse effect on the natural development. Based on the findings, architectural guidelines were established aiming to enhance the tourism development in Bislig City.